Um componente de integração entre sistemas de gestão da aprendizagem e um ambiente de aprendizagem ubíqua baseado em web services e ontologia - Carlos, Danilo Gomes (Universidade Federal Rural do Semi-Árido, 2018)
Learning Management System (LMS) are softwares used in didactic and managerial activities of the courses in distance learning, as well as in the presential and semi-presential modality. On the other hand, educational tools focusing on mobility have been gaining considerable space in this context. Ubiquitous learning environments provide a means of education independent of space and time and enable adaptation to the user context. However, the adoption of these digital tools and more dynamic educational practices end up being discouraged because there is no integration with the LMS adopted by the institution. In this sense, the present work presents the conception, development and evaluation of an integration component between Learning Management Systems and a ubiquitous learning environment, Edubi, that makes use of the Youubi API. The component makes use of web services to provide interoperability and an ontology to perform the mapping of data transported from one environment to the other. With this, it is possible to enable a range of new practices, including informal learning. In order to validate the component, the Moodle learning environment was chosen, chosen for its wide participation, including the Universidade Aberta do Brasil (UAB). The evaluation was carried out in a class of 24 students and 1 professor of the Bachelor of Science and Technology course at UFERSA. During the experiment the participants were able to use Edubi's Mobile and Web applications and Moodle simultaneously during periods outside of the classroom time. The participants of the experiment made the registration in Edubi with information provided by Moodle through the proposed component. In addition, they were able to interact with content and events imported from the Moodle environment in Edubi. With this, it was possible to use the social and gamification tools provided by Edubi in Moodle contents. The results of the evaluation performed during the experiment showed that the component provides functionalities that are useful and easy to use. It was also identified the intention to use Edubi in conjunction with Moodle by the students
Keywords: Sistema de gestão da aprendizagem; Ambiente de aprendizagem ubíqua; Integração de sistema; Web service; Ontologia; Learning management system; Ubiquitous learning environment; System integration; Web service; Ontology; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO